The role of expectations, hype and ethics in neuroimaging and neuromodulation futures - Rusconi, Elena; Mitchener-Nissen, Timothy (Frontiers in Systems Neuroscience, 2014)
The production of expectations or future-goals for the development of techniques which “read” and modulate brain function, represent an important practical tool for neuroscientists. These visions-of-the-future assist scientists by providing focus for both individual and cross-disciplinary research programs; they encourage the development of new industrial sectors, are used to justify the allocation of government resources and funding, and via the media can help capture the imagination and support of the public. However, such expectations need to be tempered by reality. Over-hyping brain imaging and modulation will lead to disappointment; disappointment that in turn can undermine its potential. Similarly, if neuroscientists focus their attention narrowly on the science without concomitant consideration of its future ethical, legal and social implications, then their expectations may remain unrealized. To develop these arguments herein we introduce the theoretical concept of expectations and the practical consequences of expectations. We contextualize these reflections by referring to brain imaging and modulation studies on deception, which encompass the measurement-suppression-augmentation range.